Ozone therapy by rectal insufflation and Minor Autohemotherapy in the management of a patient with fibromyalgia (Ozone Therapy Global Journal, 2021)
Fibromyalgia is a chronic pathology, mainly characterized by chronic musculoskeletal pain, associated with accompanying symptoms that impair the quality of life.Complementary treatment was performed with rectal ozone-therapy insufflation in patient with diagnosis of fibromyalgia, with nine years of evolution, initiated with analogous visual scale of 9/10. Thirty sessions of rectal ozone where given, three sessions per week. A decrease in pain intensity was evidenced in the fifteenth session obtained according to the 7/10 Visual Analogue Pain Scale, and in the twentieth session a decrease of Visual Analogue Pain Scale in 3/10. The quality of life improved by 80%.It can be concluded that complementary therapy with ozone could help those patients with fibromyalgia in which pain relief is not achieved with other therapies. There were no adverse effects during the treatment. Larger clinical studies are needed in this direction.